Use of Technology for HIV Prevention among Adolescent and Adult Women in the United States - Blackstock, Oni J. (Curr HIV/AIDS Rep, 2015)
Although the proportion of new HIV infections in the United States among women has decreased over the last few years, still, approximately 20% of new infections occur annually among adolescent and adult women. The development of effective evidence-based prevention interventions remains an important approach to further decreasing these numbers. Technology-delivered prevention interventions hold tremendous potential due, in part, to their ability to reach beyond the walls of brick-and-mortar intervention sites to engage individuals where they are. While most technology-delivered interventions have focused on adolescents and men who have sex with men, much fewer have specifically targeted adolescent or adult women despite evidence showing interventions tailored to specific target populations are most effective. We summarize the recently published literature on technology-delivered HIV prevention interventions for U.S. adolescent and adult women and provide suggestions for next steps in this nascent but emergent area of prevention research.